Statistics from space: Next-generation agriculture production information for enhanced monitoring of food security in Mozambique - Centro de Estudo de Políticas e Programas Agroalimentares (CEPPAG) (Universidade Eduardo Mondlane, 2024)
The Statistics from Space project (SFS) seeks to support the Government of Mozambique to produce and disseminate accurate crop production statistical data leveraging satellite remote sensing data and artificial intelligence augmented analytics. The project, funded by the Government of the Republic of Korea (Ministry of Agriculture, Food and Rural Affairs; MAFRA), aims to provide the Mozambican Ministry of Agriculture and Rural Development with production estimates of major crops across three provinces namely Gaza, Manica and Zambézia in a sufficiently timely manner so that all market participants can use the information for decision-making. SFS is a three years project and is under implementation since November 2022 by four institutions, namely the Research Centre for Agricultural Food Policy and Programs at Eduardo Mondlane University (CEPPAG), the International Food Policy Research Institute (IFPRI), the ITC at University of Twente and the Seoul National University (SNU).